He Impact of Lean Management on Achieving High Containment Practices of Workers: “An applied study on a sample of employees in telecommunications companies in Benghazi - عبد السلام الفيتوري, أشرف; أحمد الشريف, هاجر (Dirasat in Economics and Business, 2024)
The study aimed to identify the level of application of lean management and the level of high containment practices. The study population consisted of all (265) workers in the companies under study. A simple random sample method was followed; the sample size was (180) workers, and the number of valid questionnaires for analysis was (139), representing (77.2%). The study reached a set of results, the most important of which are: The level of implementation and practice of lean management in the companies under study was high, and the level of high containment practices was medium. In addition, the results showed that there is an impact of Lean management factors on the variables of high containment practices.